2021
DOI: 10.1093/bjsopen/zraa046
|View full text |Cite
|
Sign up to set email alerts
|

Economic assessment of starting robot-assisted laparoscopic inguinal hernia repair in a single-centre retrospective comparative study: the EASTER study

Abstract: Background There has been a rapid adoption of robot-assisted laparoscopic inguinal hernia repair in the USA, despite a lack of proven clinical advantage and higher material cost. No studies have been published regarding the cost and outcome of robotic inguinal hernia surgery in a European Union setting. Methods A retrospective comparative study was performed on the early outcome and costs related to laparoscopic inguinal hern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…We identified eight reports of urgent robotic operations for hernias (Table 4 ). Four studies retrospectively analyzed urgent hernia operations, two of which were controlled studies [ 25 , 40 , 41 ]. In addition, we identified a database analysis that included urgent robotic hiatal hernia operations [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified eight reports of urgent robotic operations for hernias (Table 4 ). Four studies retrospectively analyzed urgent hernia operations, two of which were controlled studies [ 25 , 40 , 41 ]. In addition, we identified a database analysis that included urgent robotic hiatal hernia operations [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lap. Vs. Open n.d No 2% overall complications; 0.1% ( n = 1) CD V More urgent and severe ill cases in open; robotic less complication than lap/open 1488 open 6774 lap n.d Muhonen et al [ 70 ] CS n.d 1 Incarcerated paraduodenal hernia Da Vinci Yes No complications 2 lap No conversions Muysoms et al [ 41 ] R-NRC 1/2016–12/2019 8 396 Robotic vs. Lap.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that the average direct cost per case in the laparoscopic repair group was $3216, compared with $3479 in the robotic group. Muysouni and colleagues reported that robot-assisted laparoscopic inguinal hernia repair was significantly more expensive than conventional laparoscopy [24]. Contributing factors to the high cost include purchasing the robot by the healthcare institution, maintenance costs, disposable materials, and longer operative times [25].…”
Section: Robotic-assisted Hernia Repair Versus Laparoscopic Repairmentioning
confidence: 99%